Implementasi Metode ROC dan WP Dalam Sistem Pendukung Keputusan Terhadap Calon Penerima Pinjaman Koperasi - Karya Suhada; Dede Hendrik; Andriyana; Evi Isnandar; Popon Dauni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Cooperatives are financial institutions that play a vital role in the economy, especially in developing countries. They provide various financial services to their members, including loans with relatively lower interest rates compared to commercial financial institutions. This study aims to develop and implement a Decision Support System (DSS) using the Rank Order Centroid (ROC) and Weighted Product (WP) methods for selecting cooperative loan recipients. Cooperatives often face challenges in determining eligible loan recipients to minimize default risk. The ROC method is used to objectively determine the criteria weights, while the WP method integrates these weights with the performance values of each candidate. By combining these two methods, it is expected to produce more accurate and fair decisions. The study was conducted in Asahan with data collected from various official sources. The criteria used include age, monthly income, employment status, credit history, and income stability. The results show that the combination of ROC and WP methods can improve the accuracy and efficiency of the cooperative loan recipient selection process and minimize the risk of default. This study contributes significantly to the field of DSS and can serve as a reference for developing decision-making methods in other fields requiring multi-criteria analysis. The findings also can be used by cooperatives to enhance the loan granting process, ensuring financial health, and member welfare. The implementation results indicate that the selected cooperative loan recipient is alternative A6, Fitriani Sari, with a score of 0.1257.